Faculdade Católica de Filosofia de Rio Grande: os primeiros anos da formação docente no ensino superior da cidade (1960-1969) - Silveira, Josiane Alves da (2012)
The current work concerns a higher education institution which represented the genesis of the teacher training oriented courses in Rio Grande city. This was the Faculdade Católica de Filosofia de Rio Grande (1960-1969), sponsored by the Mitra Diocesana de Pelotas until 1969, when it was ceded to integrate the University of Rio Grande. An analysis of its institutional history, mainly focused upon the early years of the Philosophy and Pedagogy courses. From that point, tries to ascertain the meaning and the purpose of establishing in this city, teacher training oriented courses on a high educational level. It also intends to give visibility to those who contribute to the functioning of this institution. Besides keeping alive the memory of the Catholic Faculty of Philosophy it also contributes to the History of Education with a new work concerning higher education. Emphasis is given to the lack of teacher training oriented courses at university level, until the 1960s in Rio Grande. This would have caused a repressed demand of candidates, especially women yearning for that education and training. Suggests that Mitra s pioneering action was crucial. Even so, their ambitions would not materialize without linking Rio Grande s intellectual strengths which were Education involved. It also suggests that further to the Faculty establishment the women s demand increased, probably those who where already involved with primary education. Looks for new evidences in different research sources, such as institutional documents, newspapers and oral reports. At first, institutional documents were handled at the Núcleo de Memória Engenheiro Francisco Martins Bastos (NUME) and the General Archive of the FURG. Later on, the research was extended to the newspaper Rio Grande, focused on information regarding higher education in some relevant dates for the years 1960, 1961, 1964, 1967 and 1969. Finally, eight interviews were performed with representatives of the leading board, of teaching and student staff, as well as of other officers of the Faculty. In order to do so, it takes Oral History and its conceptual categories, such as memory. Thus, assumes the paths opened by Cultural History that has also prompted further historical research problems, objects and subjects. The final considerations have found that, the articulation of catholic forces of Pelotas, as bishop Dom Antônio Zattera, with intellectuals of the Rio Grande, as Hugo Dantas Silveira, fostered the establishment and functioning of the understudy institution. In this process, others gave their contributions, many of them were actors of this institutional history. With this, the Faculty of Philosophy has enabled a greater inflow of women in higher education, the expansion of the secondary-level teaching and cultural development combined with the Church s interest of spreading the christian ideals. Furthermore, the expansion of college courses, adding six until 1969, demonstrates its potential as a teacher training institution in the city of Rio Grande.